Informed consent – A Critical Response from a Buddhist Perspective - Zhang, Ellen (Studia Bioethica, 2019)
According to the UDBHR document, “informed consent process requires of four characteristics to be valid: voluntariness, disclosure, understanding and capacity. Whenever one of these elements is missing, informed consent can be compromised.” Tom L. Beauchamp and James F. Childress in their Principle of Biomedical Ethics claim that informed consent is an individual’s autonomous authorization, whereby they postulate seven structural elements, including threshold elements (competence to understand and decide; voluntariness in deciding), information elements (disclosure of material information; recommendation of a plan; understanding of the information and recommended plan), and consent elements (decision in favor of the plan; authorization of the chosen plan).[i] In this paper I will first look at these four characteristics, and then discuss their ethical implications (for example, individual’s autonomy and human rights), followed by a critical response of these implications from a perspective of Buddhism.